Chromosome-level genome assembly of Salvia sclarea - Sehyun Choi; Yuna Kang; Changsoo Kim (Scientific Data)
Abstract Salvia sclarea is a medicinal herb from the Lamiaceae family, valued for its essential oil which contains sclareol, linalool, linalyl acetate, and other compounds. Despite its extensive use, the genetic mechanisms of S. sclarea are not well understood. This study presents a chromosome-level genome assembly of S. sclarea using the Oxford Nanopore Technology, Illumina short reads, and Pore-C technology. The assembled genome spans 499.03 Mbp with a scaffold N50 of 50.5 Mbp, forming 11 pseudochromosomes. The genome assembly was validated by BUSCO analysis, which indicated a high completeness marked at 98.7%. The genome contains 68.73% repetitive sequences, with long terminal repeats (LTRs) accounting for 33.01%. A total of 17,202 protein-coding genes were predicted. Among them, 16,846 genes were annotated in the NCBI NR database, the highest among all databases, covering 97.93% of the predicted genes. The phylogenetic analysis revealed that S. sclarea shares a close evolutionary relationship with S. officinalis within the Salvia genus, while species in the genus have evolved independently within the Lamiaceae family. This high-resolution genome assembly offers fresh insights into the biosynthesis of essential oils and other aromatic compounds in S. sclarea, establishing a basis for genetic preservation.